Inappropriate therapy of euvolemic hyponatremia, the most frequent type of hyponatremia in SARS-CoV-2 infection, is associated with increased mortality in COVID-19 patients - Pazos-Guerra, Mario; Ruiz-Sánchez, Jorge Gabriel; Pérez-Candel, Xavier; López-Nevado, Celia; Hernández-Olmeda, Fernando; Cuesta-Hernández, Martin; Martín-Sánchez, Javier; Calle-Pascual, Alfonso Luis; Runkle-de la Vega, Isabelle (Frontiers in Endocrinology, 2023)
Introduction Admission hyponatremia, frequent in patients hospitalized for COVID-19, has been associated with increased mortality. However, although euvolemic hyponatremia secondary to the Syndrome of Inappropriate Antidiuresis (SIAD) is the single most common cause of hyponatremia in community-acquired pneumonia (CAP), a thorough and rigorous assessment of the volemia of hyponatremic COVID-19 subjects has yet to be described. We sought to identify factors contributing to mortality and hospital length-of-stay (LOS) in hospitalized COVID-19 patients admitted with hyponatremia, taking volemia into account. Method Retrospective study of 247 patients admitted with COVID-19 to a tertiary hospital in Madrid, Spain from March 1st through March 30th, 2020, with a glycemia-corrected serum sodium level (SNa) < 135 mmol/L. Variables were collected at admission, at 2nd-3rd day of hospitalization, and ensuing days when hyponatremia persisted. Admission volemia (based on both physical and analytical parameters), therapy, and its adequacy as a function of volemia, were determined. Results Age: 68 years [56-81]; 39.9% were female. Median admission SNa was 133 mmol/L [131- 134]. Hyponatremia was mild (SNa 131-134 mmol/L) in 188/247 (76%). Volemia was available in 208/247 patients; 57.2% were euvolemic and the rest (42.8%) hypovolemic. Hyponatremia was left untreated in 154/247 (62.3%) patients. Admission therapy was not concordant with volemia in 43/84 (51.2%). In fact, the majority of treated euvolemic patients received incorrect therapy with isotonic saline (37/41, 90.2%), whereas hypovolemics did not (p=0.001). The latter showed higher mortality rates than those receiving adequate or no therapy (36.7% vs. 19% respectively, p=0.023). The administration of isotonic saline to euvolemic hyponatremic subjects was independently associated with an elevation of in-hospital mortality (Odds Ratio: 3.877, 95%; Confidence Interval: 1.25-12.03). Conclusion Hyponatremia in COVID-19 is predominantly euvolemic. Isotonic saline infusion therapy in euvolemic hyponatremic COVID-19 patients can lead to an increased mortality rate. Thus, an exhaustive and precise volemic assessment of the hyponatremic patient with CAP, particularly when due to COVID-19, is mandatory before instauration of therapy, even when hyponatremia is mild.